Sleep is associated with reduction of epileptiform discharges in benign adult familial myoclonus epilepsy - Takefumi Hitomi; Morito Inouchi; Hirofumi Takeyama; Katsuya Kobayashi; Shamima Sultana; Takeshi Inoue; Yuko Nakayama; Akihiro Shimotake; Masao Matsuhashi; Riki Matsumoto; Kazuo Chin; Ryosuke Takahashi; et al. (Epilepsy and Behavior Case Reports, 2019)
To clarify the effects of sleep on cortical irritability in benign adult familial myoclonus epilepsy (BAFME), we retrospectively compared epileptiform discharges of electroencephalographies (EEGs) between awake and sleep periods in 5 patients (mean age: 49.6 ± 20.3 years). We also analyzed polysomnography (PSG) of 1 patient. Epileptiform discharges were significantly more frequent during the awake period (1.3 ± 1.2/min) than those during light sleep stages (0.02 ± 0.04/min) (P < 0.05). Regarding PSG analysis, epileptiform discharges were also reduced during all sleep stages compared to those during awake periods. Our study suggests a relative reduction in cortical irritability during sleep in BAFME. Keywords: Benign adult familial myoclonus epilepsy (BAFME), Epileptiform discharges, Effects of sleep modification on cortical irritability